Environmental and Geographical Determinants of Nephrolithiasis: An Ecological Study in Kabupaten Kebumen - Eka Asmara Juhan Putra; Muhammad Irbabul Lubab (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Nephrolithiasis is a significant public health concern influenced by environmental, metabolic, and lifestyle factors. This study aimed to investigate the incidence of nephrolithiasis and its associated risk factors in karst and non-karst zones, focusing on demographic characteristics, water sources, comorbidities, and geographic variability. Understanding these determinants is crucial for developing targeted prevention strategies. Methods: A cross-sectional study was conducted from January 2025 to February 2025, involving 98 participants (35 from a karst zone and 63 from a non-karst zone). Data were collected through structured interviews, medical record reviews, and laboratory assessments, following the STROBE guidelines. Variables included age, gender, water source, daily water consumption, urinary habits, comorbidities, and occupational environment. Statistical analyses were performed using RStudio, with Mann-Whitney U tests for continuous variables and logistic regression for categorical variables. Nephrolithiasis incidence rates were calculated per 100,000 population and visualized using a heatmap. Result: District-specific incidence ranged from 10,989.0 (Ayah, karst; Karanganyar, non-karst) to 1,098.9 (Prembun, non-karst) per 100,000 population. Unadjusted risk-ratio (RR) estimates (95 % CI) included: female sex RR 1.52 (0.52–4.42); groundwater vs distilled water RR 1.65 (0.43–6.35); municipal vs distilled water RR 0.26 (0.03–2.12); fluid intake < 2,500 mL vs ≥ 2,500 mL RR 0.96 (0.32–2.81); urine retention RR 1.07 (0.38–3.03); outdoor vs indoor work RR 1.52 (0.52–4.42); scale present on boiling water RR 3.27 (0.88–12.24). None of the adjusted models reached statistical significance. Conclusions: This study underscores the multifactorial etiology of nephrolithiasis, emphasizing the role of geological, metabolic, and lifestyle factors. Targeted interventions, including community screening, dietary modifications, and improved water quality, are essential for reducing disease burden. Future research should explore causal relationships and refine preventive strategies through longitudinal studies and larger cohorts. These findings contribute to a deeper understanding of nephrolithiasis and inform region-specific public health measures.